2022
DOI: 10.3390/ijerph19020941
|View full text |Cite
|
Sign up to set email alerts
|

The Cool Kids as a School-Based Universal Prevention and Early Intervention Program for Anxiety: Results of a Pilot Study

Abstract: The efficacy of the Cool Kids program has been consistently demonstrated both within Australia and internationally, but limited data are available on the use of Cool Kids as a universal program. The purpose of the study is to evaluate Cool Kids as a universal program for preventing childhood anxiety in the school context. There were 73 Italian children (35 boys and 36 girls, ages 10–13 years) attending the last year of primary school and the first year of middle school who participated in an active interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 71 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…Therefore, an overall score, which was well-supported across cultures (e.g., Isolan et al, 2011), would be employed. The employment resonated past examinations of CBT therapeutic changes in adolescent anxiety (e.g., Scaini et al, 2022).…”
Section: The Current Studymentioning
confidence: 82%
See 1 more Smart Citation
“…Therefore, an overall score, which was well-supported across cultures (e.g., Isolan et al, 2011), would be employed. The employment resonated past examinations of CBT therapeutic changes in adolescent anxiety (e.g., Scaini et al, 2022).…”
Section: The Current Studymentioning
confidence: 82%
“…Group members could assist one another in this process through scaffolding (McLeod, 2012 ). With these benefits, the group format was adopted by various CBT-based anxiety intervention programs for adolescents (e.g., Lau et al, 2010 ; Scaini et al, 2022 ) and well supported by empirical evidence (Ginsburg & Drake, 2002 ; Herzig-Anderson et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this line, preventive and therapeutic programs aimed at the management of anxiety, school refusal (Estévez et al, 2009; Galán‐Luque, 2023; Gonzálvez, Ingles, & García‐Fernández, 2018; Mateu‐Martínez et al, 2013; Scaini et al, 2022), and social skills programs in childhood and adolescence (Ingles, 2011; Ugarte‐Paz et al, 2021) have shown the importance of teaching and acquiring social skills (Huber et al, 2019; Sklad et al, 2012) and strategies for emotion self‐regulation or anxiety reduction (Gallegos et al, 2012) as of early childhood. This would enhance the academic adaptation and personal well‐being of Spanish children in primary education.…”
Section: Discussionmentioning
confidence: 99%